فاعلية الارشاد المدرسي من وجهة نظر عينة من اساتذة التعليم الثانوي بالاأغواط - محمد تومي; ديدة بقوقة; بوداود حسين (My University, 2023)
The current study aimed to know the attitudes of teachers towards the effectiveness of school counseling. This study was applied to a sample consisting of (60) teachers of different specializations in the secondary stage who practice their work in three secondary schools in the state of Laghouat for the academic year (2022/2023). They were chosen randomly, and we relied in our study on The analytical descriptive approach that serves our study, and to achieve the objectives of the study, then use a questionnaire that includes (20) statements distributed on two axes, apply the questionnaire after subjecting it to procedures of validity and reliability, and after statistical treatment through the (spss) program, the study reached the following results: • There is a high level of school counseling according to teachers' perspective among secondary education students. • There are differences in teachers’ attitudes towards the effectiveness of school guidance due to gender. • There are differences in teachers’ attitudes regarding the effectiveness of school guidance due to specialization. • There are differences in teachers’ attitudes towards the effectiveness of school guidance due to seniority. • Keywords: school counseling, education, guidance, educational process, secondary education